2019
DOI: 10.1177/1060028019854221
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis: Effects on Opioid and Benzodiazepine Requirements for Pain Control

Abstract: Background: There is currently little evidence regarding the use of medical cannabis for the treatment of intractable pain. Literature published on the subject to date has yielded mixed results concerning the efficacy of medical cannabis and has been limited by study design and regulatory issues. Objective: The objective of this study was to determine if the use of medical cannabis affects the amount of opioids and benzodiazepines used by patients on a daily basis. Methods: This single-center, retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
1
20
1
Order By: Relevance
“…Previous research studies have reported a level of substantial evidence for medical cannabis’ use in the alleviation of pain [ 5 , 27 , 29 ]. Both Canadian clinicians [ 5 ] and the NASEM [ 30 ] have concurred that medical cannabis use may be effective in the management of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research studies have reported a level of substantial evidence for medical cannabis’ use in the alleviation of pain [ 5 , 27 , 29 ]. Both Canadian clinicians [ 5 ] and the NASEM [ 30 ] have concurred that medical cannabis use may be effective in the management of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…); (2) mental health conditions [12][13][14][15] (anxiety [16,17], depression [18,19]); (3) autoimmune disorders [20]; (4) sleep problems [21,22]; (5) neurological [23]; (6) gastrointestinal [24]; and (7) other health conditions [25,26] such as chemo-induced nausea/vomiting [7]. There also has been an increasing frequency of medical cannabis use as an alternative to opioids [11,18,27] for patients. With the exception of neuropathic chronic pain [10], chemotherapy-induced nausea/vomiting [28], and certain spasticity symptoms, the majority of previous studies concur that there is currently very weak evidence regarding its clinical effectiveness for its long-term use [23].…”
Section: Introductionmentioning
confidence: 99%
“…The positive bi-directional association between benzodiazepines and analgesics is supported by many previous studies (37)(38)(39). However, others have found a negative association between the use of cannabis and benzodiazepines (40,41), and have identified a substitutional role between them (42). These findings could explain the negative bi-directional relationship found in the present study.…”
Section: Discussionmentioning
confidence: 60%
“…opiates, anti-depressants, nonopioid pain medicine), alcohol, and illicit substances) (Lucas et al 2019). Education regarding the therapeutic benefits of cannabis and proper ways to administer cannabis may change attitudes and downstream cannabis use behavior reducing the adverse effects of cannabis (O'Connell et al 2019).…”
Section: Introductionmentioning
confidence: 99%